Optimasi Suhu dan Lama Pengeringan pada Pembuatan Komposit Bioplastik Campuran Maizena dan Glukomanan - Pongmassangka, Liza Natasya; Harsojuwono, Bambang Admadi; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 3 (2020): September, 2020)
This study aims to determine the effect of temperature regulation and the appropriate drying time on the manufacture of bioplastic composites of maize and glucomannan mixtures, as well as providing information on science and technology in the field of bioplastics. This experimental design uses the complete random design method. The first factor is the drying temperature of bioplastic composites from a mixture of cornstarch and glucomannan which consists of 3 levels, namely 60 ± 1; 65 ± 1; 70 ± 1 ° C. Factor 2 is the drying time which consists of 3 levels, namely for 16, 17.5 and 19 hours. The variables observed were tensile strength, elongation at break, elasticity, swelling and biodegradation. Data were analyzed for diversity and continued with the Tukey test to find out the difference of design experiment. The results showed that temperature and drying time and their interactions had a very significant effect on tensile strength, elongation, elasticity, and water absorption. but the temperature treatment and interaction have no significant effect on the ability of biodegradation. The interaction between treatments has a very significant effect on elongation, elasticity and water absorption. and has a significant effect on tensile strength. The best biodegradable plastic characteristics were determined by tensile strength test at a temperature of 70 °C with 16 hours drying time which resulted in tensile strength values ??of 2,395MPa. Bioplastics produced in this study did not meet the criteria of mechanical tensile strength, elasticity and thickness development. Keywords: Bioplastics, glycerol, glucomannan and maizena.